Traditional Ecological Knowledge of Polar Bears in the Northern Eeyou Marine Region, Québec, Canada - Laforest, Brandon J.; Hébert, Julie S.; Obbard, Martyn E.; Thiemann, Gregory W. (ARCTIC, 2018)
Polar bears are important socio-cultural symbols in the communities of the Eeyou Marine Region (EMR) in northwestern Québec, Canada. Members of the Cree communities in this region are generally not active polar bear hunters, but they encounter polar bears when fishing, trapping, or hunting during the ice-free season. A growing body of scientific evidence suggests that reduced annual sea ice cover in Hudson Bay has led to declines in body condition of polar bears in the local Southern Hudson Bay subpopulation and to a population decline in the neighboring Western Hudson Bay subpopulation. In June 2012, we conducted 15 semi-directed interviews on the subject of polar bear biology and climate change with local elders and hunters in three communities in the northern EMR: Wemindji, Chisasibi, and Whapmagoostui. The interviews held in Whapmagoostui included informants from Kuujjuarapik, the adjacent Inuit community. The interviews addressed knowledge gaps in the Recovery Strategy for Polar Bear in Ontario. Transcripts of the interviews were coded thematically and analyzed using both qualitative and quantitative methods. The interviews revealed important insights into polar bear distribution, terrestrial habitat use, denning, and foraging patterns. Participants were unanimous in their recognition of a warming climate and prolonged ice-free season in the area in recent years. However, communities differed in their observations on other issues, with latitudinal trends evident in observations of polar bear distribution, denning activity, and foraging habits. Communities also differed in their perception of the prevalence of problem polar bears and the conservation status of the species, with one-third of participants reporting that polar bears will be unaffected by, or even benefit from, longer ice-free periods. A majority of participants indicated that the local polar bear population was stable or increasing. Interviewees also identified future research priorities pertinent to the communities, and provided comments on ...